Coral Morphology Portrays the Spatial Distribution and Population Size-Structure Along a 5–100 m Depth Gradient - Kramer, Netanel; Tamir, Raz; Eyal, Gal; Loya, Yossi (Frontiers in Marine Science, 2020)
Population size structure provides information on demographic characteristics, such as growth and decline, enabling post-hoc assessment of spatial differences in susceptibility to disturbance. Nevertheless, very few studies have quantified size data of scleractinian corals along a shallow-mesophotic gradient, partly because of previously inaccessible depths. Here, we report the coral size-frequency distributions at the morphology level (six growth forms) and at the species level for ten representative locally species along a broad depth gradient (5-100 m) in the Gulf of Eilat/Aqaba (GoE/A). A total of 18,865 colonies belonging to 14 families and 45 genera were recorded and measured over four reef sites. Colonies were found to be 11.2% more abundant at mesophotic (40-100 m; 55.6%) depths compared with shallow (5-30 m; 44.4%). The coral taxa exhibited heterogeneity in their size-structure, with marked differences among depths, morphological growth forms, and species. Branching and corymbose corals were more prevalent in shallow waters, while encrusting and laminar forms comprised the majority of mesophotic corals. Nevertheless, massive morphology was the most abundant growth form across all sites and depths (39%), followed by laminar (26%) and encrusting (20%). Corymbose corals (primarily Acroporidae) revealed constrained size at all depths; with the lack of small-size groups indicating populations at risk of decline. Depth-generalist species belonging to massive and laminar morphologies generally exhibited a larger colony size at the mesophotic depths, but were typified by a higher number of small colonies. Furthermore, we refute the widely and long-accepted assertion that Stylophora pistillata is the most abundant coral in the northern GoE/A, and assert that Leptoseris glabra is the one. Here, we provide a baseline for future monitoring of coral population structures, insights to recent ecological dynamics, retrospective assessment of coral community recovery following disturbances and grounds for conservation assessments and management actions.